CGIAR Climate Impact Platform MELIA Framework - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
The theory of change (Annexed) outlines how the Climate Impact Platform contributes to global climate goals through five key impact pathways: 1)Research to Action: The platform leverages cutting-edge research to develop and apply climate adaptation and mitigation technologies. Its "Expertise and Themes" subsystem, which organizes scientists and enhances their expertise, is central to this process. - Function: Organizing scientists into thematic groups and enhancing their expertise. - Facilitation: Providing expertise and insights for innovative research development. - Mediators: Research outputs. - Moderators: Resource availability and technology adoption rates.